SAWAH POKOK MURAH IN WEST SUMATRA: A LOCALIZED, SUSTAINABLE ALTERNATIVE TO THE CAPITALIST GLOBAL FOOD SYSTEM - Setyaka, Virtuous; Andrezal, Andrezal; Yulianti, Dina; Bainus, Arry; Indrayani, Irma (Universitas Nasional, 2025)
This article explores the Sawah Pokok Murah (SPM) initiative in West Sumatra as a localized, reconstructive response to the capitalist-driven global food system. Through a historical sociology approach and food sovereignty framework, the study investigates how SPM challenges structural inequalities in global food markets by promoting sustainable farming practices and community empowerment. The paper analyzes the historical context of SPM, its socio-economic impact, and its role in resisting neoliberal agricultural policies. Key findings reveal that SPM empowers local farmers, reduces dependency on global supply chains, and fosters economic resilience, thereby providing a viable alternative to market-driven agriculture. However, challenges such as youth engagement and regional disparities highlight the need for targeted policy interventions. This study contributes to the discourse on food sovereignty and offers a critical perspective on how localized innovations can reshape global agricultural systems toward greater sustainability and equity.